Deterministic switching of antiferromagnetic spin textures by nonlinear magnons - Jilei Chen; Mingran Xu; Jinlong Wang; Kai Wagner; Lutong Sheng; Hao Jia; Weiwei Wei; Han Zhang; Yuelin Zhang; Hanchen Wang; Rundong Yuan; Mohammad Hamdi; et al. (Nature Communications)
Abstract Antiferromagnetic spin textures, compared to their ferromagnetic counterparts, innately possess high stability with respect to external disturbance and high-frequency dynamics compatible with ultrafast information processing. However, deterministic creation and reconfigurable switching of different antiferromagnetic spin textures have not been realized. Here, we demonstrate room-temperature deterministic switching between three antiferromagnetic textures identified by characteristically different high frequency dynamics in single-crystal hematite (α-Fe2O3). All three states are found to be remarkably stable and fully controllable, as confirmed by 1000 switching cycles and spatially resolved spectroscopy and they may be created by local magnetization switching in the nonlinear excitation regime. The switching to the following stable state requires only one microwave pulse (100 ns) with ultralow energy consumption (1 nJ). Our Brillouin light scattering (BLS) microscopy data reinforces that the detected magnon modes are associated to excitations of domain walls and circular spin textures. The progressive switching between the three distinct states imitates the weighted sum operation in neuromorphic computing, suggesting the possibility of using spin textures in antiferromagnets for information processing.